The implication and evaluation of geometrical imperfections on manufactured surfaces. Issue 2 (2022) - Mullany, B.; Savio, E.; Haitjema, H.; Leach, R.
Abstract: This paper takes the broad topic of geometrical surface imperfections on manufactured surfaces and provides an overview of how they affect component functionality and how they may be detected and classified as defects or not. The presented overview considers both human visual inspection and machine vision-based approaches along with their evolving roles. Of note is that the paper takes a highly granular field consisting of customized solutions for customized applications and frames the discussion around fundamental considerations for each of the tasks; search/acquisition, sensing/detection, processing, classification and decision. Future trends and areas still requiring attention are highlighted.